Comportamiento epidemiológico temporo-espacial y factorial de la Varicela en la provincia de Loja, periodo 2018 al 2022 - Apolo Bravo, Emily Valeria (2024)
Chickenpox is an infectious disease caused by the varicella-zoster virus, characterized by the progressive appearance of macules, papules, vesicles and crusts, along with itching. In Latin America, reported cases have decreased due to the implementation of the vaccine, and in Ecuador, cases are reported through the SIVEA – Alert system according to the area of residence. Therefore, the purpose of this research focused on characterizing the epidemiological behavior of chickenpox in the inhabitants of the province of Loja in order to implement prevention and detention measures from 1028 to 2022. An analytical study with a mixed approach and cross-sectional cohort design was conducted on a sample of 702 cases recorded in the open database on the Ministry of Public Health (by its acronym in Spanish, MSP); of which 57.1% of the cases were men, 25.8% were between 20 and 49 years old, and 63% were registered in the canton of Loja. The highest number of reports was found in 2018, mainly during the dry and cold seasons. Consequently, a digital educational proposal was developed, aimed at the prevention and health promotion of this infectious disease